2012
DOI: 10.1681/asn.2011101006
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Deficiency Reduces Circulating Levels of FGF23

Abstract: Fibroblast growth factor (FGF) 23 inhibits calcitriol production, which could exacerbate calcium deficiency or hypocalcemia unless calcium itself modulates FGF23 in this setting. In Wistar rats with normal renal function fed a diet low in both calcium and vitamin D, the resulting hypocalcemia was associated with low FGF23 despite high parathyroid hormone (PTH) and high calcitriol levels. FGF23 correlated positively with calcium and negatively with PTH. Addition of high dietary phosphorus to this diet increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
106
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(135 citation statements)
references
References 25 publications
21
106
2
1
Order By: Relevance
“…In addition, hPTH (1-34) treatment only partially recovered the decrease in plasma calcium levels induced by CIN treatment, although hPTH (1-34) administration at the same dose used in the present study has been reported to effectively increase plasma calcium levels in rats (18). These findings suggested that CIN treatment may have decreased plasma FGF23 levels by decreasing plasma calcium levels and by decreasing PTH secretion; thus the inhibitory effects of hypocalcemia on FGF23 secretion may have overwhelmed the stimulatory effect of hPTH (1-34), which supports the proposition by Rodriguez-Ortiz et al (28) that hypocalcemia limits phosphorus-induced FGF23 production. Nemeth et al (16) reported that CIN administration at the same dose used in the present study not only decreased serum PTH levels but also increased serum calcitonin levels in rats.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, hPTH (1-34) treatment only partially recovered the decrease in plasma calcium levels induced by CIN treatment, although hPTH (1-34) administration at the same dose used in the present study has been reported to effectively increase plasma calcium levels in rats (18). These findings suggested that CIN treatment may have decreased plasma FGF23 levels by decreasing plasma calcium levels and by decreasing PTH secretion; thus the inhibitory effects of hypocalcemia on FGF23 secretion may have overwhelmed the stimulatory effect of hPTH (1-34), which supports the proposition by Rodriguez-Ortiz et al (28) that hypocalcemia limits phosphorus-induced FGF23 production. Nemeth et al (16) reported that CIN administration at the same dose used in the present study not only decreased serum PTH levels but also increased serum calcitonin levels in rats.…”
Section: Resultssupporting
confidence: 87%
“…In the present study, hPTH (1-34) administration in CIN-treated rats partially recovered the decrease in plasma FGF23 levels, which could be explained by the following two possibilities: first, plasma hPTH (1-34) levels increased in a transient manner, which may not have been sufficient to continuously recover the decrease in plasma FGF23 levels; second, CIN treatment inhibited the increase in plasma FGF23 levels by another mechanism in addition to inhibition of PTH secretion. Rodriguez-Ortiz et al (28) reported that hypocalcemia reduced circulating FGF23 levels. In the present study, plasma calcium levels in CIN-treated rats continued to decrease until 2 h after oral phosphorus administration and afterward, they remained lower for at least 6 h compared with the 0 time point (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data, support recent experimental evidence pointing to interactions between calcium and phosphorus in the regulation of FGF-23 production (50,51). Because increases of FGF-23 in renal transplant patients have been correlated with both poor graft function and patient survival (52), it is reassuring that levels remained low.…”
Section: Evenepoel Et Alsupporting
confidence: 81%
“…However, the trend towards hypocalcemia as a result of FGF23-mediated suppression of vitamin D activation may increase PTH levels [19,38]. Finally, the presence of diabetes correlated inversely with PTH levels.…”
Section: Resultsmentioning
confidence: 99%
“…G3a (Mildly to moderately decreased, 45-59), G3b (Moderately to severely decreased, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], G4 (Severely decreased [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and G5 (Kidney failure <15). CKD is defined as either an eGFR <60 ml/min/1.73 m 2 or evidence of kidney injury such as a urinary albumin/creatinine ratio (UACR) >30 mg/g [1].…”
Section: The Kdigo 2012 Clinical Practice Guidelines For the Evaluatimentioning
confidence: 99%